Low Vision Service Reimbursement Plan for Each Canadian Province - Hong, Yejun; Swift, Andrew; Luong, Micah (Canadian Journal of Optometry, 2022)
The increasing low vision patients in the world encounter several barriers that prevent them seeking treatment. In Canada, such barriers stem from patients’ circumstances, stigma in the community or from factors that discourage eye care professionals from providing low vision services. Remuneration plans for low vision services are inconsistent and insufficient between provinces or territories. One method for our health care systems to enhance accessibility and equity of low vision services would be by providing adequate reimbursements to eye care professionals who spend extra time and care to conduct such crucial service.